2017
DOI: 10.1371/journal.pone.0189276
|View full text |Cite
|
Sign up to set email alerts
|

Efficient visible light photocatalysis of benzene, toluene, ethylbenzene and xylene (BTEX) in aqueous solutions using supported zinc oxide nanorods

Abstract: Benzene, toluene, ethylbenzene and xylenes (BTEX) are some of the common environmental pollutants originating mainly from oil and gas industries, which are toxic to human as well as other living organisms in the ecosystem. Here we investigate photocatalytic degradation of BTEX under visible light irradiation using supported zinc oxide (ZnO) nanorods grown on glass substrates using a microwave assisted hydrothermal method. ZnO nanorods were characterized by electron microscopy, X-ray diffraction (XRD), specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…The conduction band (CB) potentials were -0.43 eV for CuO and -0.15 eV for ZnO vs Normal Hydrogen Electrode (NHE) [40]. The band gaps of CuO and ZnO were 1.4 and 3.23 eV, respectively [41,42]. During sunlight irradiation, CuO and ZnO were excited to generate electrons and holes at the CB and the valence band (VB), respectively, as displayed in Figure 8, since the band positions of ZnO were below the CB and VB of CuO.…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…The conduction band (CB) potentials were -0.43 eV for CuO and -0.15 eV for ZnO vs Normal Hydrogen Electrode (NHE) [40]. The band gaps of CuO and ZnO were 1.4 and 3.23 eV, respectively [41,42]. During sunlight irradiation, CuO and ZnO were excited to generate electrons and holes at the CB and the valence band (VB), respectively, as displayed in Figure 8, since the band positions of ZnO were below the CB and VB of CuO.…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…Viral load as the initial pollutant concentration can affect the performance of photocatalytic processes. Many studies have investigated the effect of initial load of organic pollutants (e.g., benzene, toluene, and other pollutants) on the photocatalytic process efficiency (Al-Sabahi et al 2017 ; Einaga et al 2004 ). Regarding the effect of initial viral load, Yu et al used a reactor equipped with two ultraviolet lamps and a TiO 2 filter at 365 nm wavelength for the removal of various types of airborne microorganisms and showed that the photocatalytic filter was able to remove about 36% of the airborne phages with an initial viral load of 8.7 × 10 4 -1.2 × 10 7 .…”
Section: Viral Loadmentioning
confidence: 99%
“…This dual‐functionalized NF filter showed enhanced PM filtration performance, as well as high‐toluene decomposition efficiency under xenon light irradiation 3 . Similarly, ZnO has been widely used for the efficient degradation of organic contaminants 28–32 . For instance, Ghanbari et al 33 reported the photocatalytic activity of ZnO nanorods, grown on alumina microfiber surface for both liquid phase and gas phase decompositions of methylene blue (MB) and toluene, respectively 29 .…”
Section: Introductionmentioning
confidence: 98%
“…3 Similarly, ZnO has been widely used for the efficient degradation of organic contaminants. [28][29][30][31][32] For instance, Ghanbari et al 33 reported the photocatalytic activity of ZnO nanorods, grown on alumina microfiber surface for both liquid phase and gas phase decompositions of methylene blue (MB) and toluene, respectively. 29 Their results showed almost complete decomposition of the organics after 10-20 min of exposure to UV light irradiation.…”
mentioning
confidence: 99%